2017
DOI: 10.1007/s00262-017-2100-1
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical natural killer cells induce remissions in non-Hodgkin lymphoma patients with low levels of immune-suppressor cells

Abstract: We report a novel phase 2 clinical trial in patients with poor prognosis refractory NHL testing the efficacy of haploidentical donor NK cell therapy (NK dose 0.5–3.27 × 107 NK cells/kg) with rituximab and IL-2.(clinicaltrials.gov NCT01181258) Therapy was tolerated without graft-versus-host-disease, cytokine release syndrome, or neurotoxicity. Of 15 evaluable patients, 4 had objective responses (26.6%) at 2 months: 2 had complete response lasting 3 and 9 months. Circulating donor NK cells persisted for at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…18,42 In several trials testing efficacy of haploidentical NK cells in patients with advanced relapsed or refractory tumors, responses were observed only in a small subgroup of patients and were hampered by co-expansion of Tregs which were thought to be of patient origin. 43-46 Our results suggest that expansion of Tregs may arise in the tumor microenvironment upon PD-L1 expression, and can even occur by expansion from the very small amount of T cells transferred as part of an adoptive NK cell product. To mitigate such in situ Treg generation, PD-L1 blockade may prevent Tregs induction and improve overall efficacy of adoptive NK cell therapy.…”
Section: Discussionmentioning
confidence: 82%
“…18,42 In several trials testing efficacy of haploidentical NK cells in patients with advanced relapsed or refractory tumors, responses were observed only in a small subgroup of patients and were hampered by co-expansion of Tregs which were thought to be of patient origin. 43-46 Our results suggest that expansion of Tregs may arise in the tumor microenvironment upon PD-L1 expression, and can even occur by expansion from the very small amount of T cells transferred as part of an adoptive NK cell product. To mitigate such in situ Treg generation, PD-L1 blockade may prevent Tregs induction and improve overall efficacy of adoptive NK cell therapy.…”
Section: Discussionmentioning
confidence: 82%
“…[reviewed in Paul and Lal (37)]. The infusion of HLA mismatched NK cells has led to promising clinical results, confirming a direct anti-neoplastic effect (38,39). Hence, the respective impacts of T-cell and NK-cell reactivity in HLA mismatched transplants and other cell therapy approaches are still unknown but may account for the effects on GVT and GVHD observed in haplo-identical and cord blood transplants.…”
Section: Target Antigens In Hematological Cancers Histocompatibility mentioning
confidence: 99%
“…After NK cell transplantation, leukaemia‐associated transcripts disappeared in elderly patients. Most recently, it was shown that haploidentical NK cells induce remissions in non‐Hodgkin's lymphoma patients (Bachanova et al, ). These studies point to the utility of allogeneic NK‐cell transplants in the antitumour response in a variety of cancers.…”
Section: Adoptive Nk‐cell Therapymentioning
confidence: 99%